Under the bombs : the German home front; 1942 - 1945 - Beck, Earl R. 1916-2002 (Univ. Pr. of Kentucky, 1986)
Klappentext: Under the Bombs tells the story of the civilian population of German cities devastated by Allied bombing in World War II. These people went to work, tried to keep a home (though in many cases it was just a pile of rubble where a house once stood), and attempted to live life as normally as possible amid the chaos of war. Earl Beck also looks at the food and fuel rationing the German people endured and the problems of trying to make a public complaint while living in a totalitarian state.